The Johannine Son of Man: A New Proposal - Ashton, John (New Testament studies, 2011)
How is the association of the descent/ascent motif with the Johannine Son of Man to be explained if the gnosticism theory no longer holds? ἀναβέβηκεν (3.13) is usually taken to refer to Jesus' final ascension. But Odeberg saw that it refers to a tradition of heavenly ascent in Jesus' lifetime. Bühner argued rather for a double reference—to the ascent of a visionary seer involving a metamorphosis into a heavenly being and a final ascent at death. Yet he ignores the likelihood, sustained by Jarl Fossum and Morton Smith, that the transfiguration tradition was based on an authentic memory. In chs. 9 and 5 the evangelist recognizes that Jesus had been invested with the authority of the heavenly Son of Man. He sees the crucifixion as an exaltation (3.14), and follows a statement of Jesus' ascent, descent and exaltation by a full summary of God's loving gift to the world.